Eufemisme dalam Wacana Berita Online Riau Pos.com - Fira Andarina Zaharnika, R.; Nazirun, Nazirun (J-LELC: Journal of Language Education, Linguistics, and Culture, 2023)
The use of good and correct language can be done by avoiding the use of impolite language. This is done so that the words spoken do not offend others. For this reason, the problem in this study is how is the form of euphemism in discourse in online news riau pos.com? This term is called euphemism. Refinement of the meaning of words is a common phenomenon in society. The research method used by the author is descriptive (to describe or describe existing phenomena). Data collection techniques are documentation techniques and hermeneutic techniques. Data analysis techniques used are collection, grouping based on groups, presentation, and drawing conclusions. The results of the research data in this writing are that the most forms of euphemisms in discourse in the Riau Pos.com newspaper are euphemisms using abbreviations, namely 10, euphemisms for using foreign terms as many as 7, metaphorical euphemisms as many as 11. So it can be concluded that euphemisms avoid meaning ambiguous. Loudness is often found, because the media uses euphemisms for things that are more polite to convey and also avoid things that are not desirable.